IN SEARCH OF A BULK-EARTH COMPOSITION - Hart S.R.; Zindler A. (My University, 1986)
Refined estimates of primitive upper-mantle (PUM) composition are derived here from the major-element and rare-earth-element (REE) contents of mantle lherzolites, using the approaches pioneered by Loubet et al. (1975) and Jagoutz et al. (1979). Because the PUM composition of Jagoutz et al. (1979) is distinctly non-chondritic in certain “refractory” element ratios, such as Mg/Si and Ca/Al, either the upper and lower mantles are chemically different, or the bulk silicate Earth (BSE) is non-chondritic with respect to these elements. We argue that the high Ca/Al ratios observed in lherzolites are not in fact representative of PUM composition, but are caused by excess and non-representative modal abundances of clinopyroxene in analyzed lherzolite samples. Corrections for this excess Cpx lead to REE ratios (to Ca or Al) in the least depleted lherzolites which are essentially chondritic.